ALBI score and outcomes in patients with hepatocellular carcinoma: post hoc analysis of the randomized controlled trial KEYNOTE-240. (September 2021) - Vogel, Arndt; Merle, Philippe; Verslype, Chris; Finn, Richard S.; Zhu, Andrew X.; Cheng, Ann-Lii; Chan, Stephen Lam; Yau, Thomas; Ryoo, Baek-Yeol; Knox, Jennifer; Daniele, Bruno; Qin, Shukui; et al.
Aims: This post hoc analysis evaluated albumin/bilirubin (ALBI) score, an objective measure of liver function, in patients receiving pembrolizumab plus best supportive care (BSC) compared with placebo plus BSC in the KEYNOTE-240 study. Methods: Patients with confirmed hepatocellular carcinoma (HCC) and progression after/intolerance to sorafenib, Child–Pugh class A liver function, and Eastern Cooperative Oncology Group performance status of 0–1 were randomly assigned 2:1 to pembrolizumab 200 mg or placebo intravenously every 3 weeks plus BSC for ⩽35 cycles or until confirmed progression/unacceptable toxicity. Outcomes were assessed by ALBI grade. Results: Of 413 patients, at baseline 116 had an ALBI grade 1 score (pembrolizumab, n  = 74; placebo, n  = 42) and 279 had an ALBI grade 2 score ( n  = 193; n  = 86). Change from baseline in ALBI score to the end of treatment was similar in both arms [difference in least squares mean, −0.039; 95% confidence interval (CI): −0.169 to 0.091]. Time to ALBI grade increase was similar in both arms [median for pembrolizumab versus placebo: 7.8 versus 6.9 months; hazard ratio (HR) = 0.863 (95% CI: 0.625–1.192)]. Regardless of baseline ALBI grade, a trend toward improved overall survival was observed with pembrolizumab [grade 1: HR = 0.725 (95% CI: 0.454–1.158); grade 2: HR = 0.827 (95% CI: 0.612–1.119)]. Conclusion: Pembrolizumab did not adversely impact liver function compared with placebo in patients with HCC, as measured by changes in ALBI scores. A trend toward improved overall survival was observed with pembrolizumab in both ALBI grade groups. ClinicalTrials.gov identifier : NCT02702401.